Inside Cover: MAGBONS: Novel Magnetically Separable Carbonaceous Nanohybrids from Porous Polysaccharides (ChemCatChem 10/2014). Issue 10 (October 2014) - Ojeda, Manuel; Balu, Alina Mariana; Romero, Antonio Angel; Esquinazi, Pablo; Ruokolainen, Janne; Sixta, Herbert; Luque, Rafael
<x xml:space="preserve">Abstract</x> My name is BON, MAGBON The cover picture shows novel and versatile magnetically separable carbonaceous materials that have been synthesized using a simple methodology from native starch. In their Full Paper on p. 2847 ff., M. Ojeda et al. describe functionalized MAGBONs that exhibit promising catalytic activities in oxidation reactions.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>